Entrepreneurs’ Ethnic and Political Identity Alignment as Determinants of Access to Government Support in Africa: A Conceptual Framework - Abebe, Michael A.; Getachew, Yamlaksira S.; Kimakwa, Sarah (Entrepreneurship Theory and Practice, 2022)
This article contributes to research on the role of government in entrepreneurship by extending the current focus from government policies to policymakers. Specifically, we examine how entrepreneurs’ identity alignment with regime leaders influences their access to government support in Africa. Drawing from ethnocentrism and neopatrimonialism perspectives, we develop a theoretical model that explains how entrepreneurs’ ethnic and political identity alignment influences their access to government support. We also advance theory by discussing the “dark side” of identity-based government support in Africa. In doing so, we shed some light on the rather complex sociopolitical determinants of resource access in Africa.